Estimation of Stature from Head Length and Head Breadth in Undergraduate Medical Students: An Anthropometric Study - Pandey, Niraj; Mani Chaudhary, Deepak; Yadav, Sanjay Kumar (Medical Journal of Eastern Nepal, 2024)
Background: Height is a significant parameter for growth and development of an individual. The aim of our study is to estimate stature from Head Length (HL) and Head Breadth (HB) in living and to derive the correlation and regression formulae between them. Methods: This is a descriptive study. A total of one hundred and ninety four medical students, presently studying at Devdaha Medical College and Research Institute, aged between eighteen and twenty four years were selected as the subjects for the present study. Two skull measurements namely head length and head breadth were taken by following standards- Anthropometric methods and technique and the Standing height was measured using a stadiometer. Results: The Regression equation for stature of males using head length is 153.02+0.75HL and using head breadth is 141.65+1.67HB. The regression equation for stature in females using head length and breadth are 100.837+3.081HL and 112.23+3.002HB respectively. Conclusion: From our study we conclude that there is a weak positive correlation between height and head length in both males and females. The data obtained may be useful in anthropological research, forensic, genetic research, as well as in medical clinical practice.